2016
DOI: 10.1002/cncr.29957
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhancing tumor growth dynamics of preoperative, treatment‐naive human glioblastoma

Abstract: BACKGROUND:Little is known about the natural growth characteristics of untreated glioblastoma before surgical or therapeutic intervention, because patients are rapidly treated after preliminary radiographic diagnosis. Understanding the growth characteristics of uninhibited human glioblastoma may be useful for characterizing changes in response to therapy. Thus, the objective of the current study was to explore tumor growth dynamics in a cohort of patients with untreated glioblastoma before surgical or therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 16 publications
1
37
0
1
Order By: Relevance
“…For example, the current RANO criteria requires use of bidirectional measurements of contrast enhancing tumor size, which have been shown to overestimate tumor volume [53] and result in higher reader discordance [8, 5459], presumably due to differences in head tilt and accurate identification of longest and perpendicular diameter in relatively irregular tumors. Other studies have shown reasonable agreement between bidimensional and volumetric measurements [60, 61], suggesting quick bidimensional assessment of contrast enhancing tumor size may be a practical alternative to more sophisticated volumetric segmentation. Additionally, the thresholds used to define response and progression is relatively arbitrary and not optimized based on scientific data showing the best correlation with survival benefit or time to treatment failure.…”
Section: Known Limitations For Current Response Criteriamentioning
confidence: 80%
See 1 more Smart Citation
“…For example, the current RANO criteria requires use of bidirectional measurements of contrast enhancing tumor size, which have been shown to overestimate tumor volume [53] and result in higher reader discordance [8, 5459], presumably due to differences in head tilt and accurate identification of longest and perpendicular diameter in relatively irregular tumors. Other studies have shown reasonable agreement between bidimensional and volumetric measurements [60, 61], suggesting quick bidimensional assessment of contrast enhancing tumor size may be a practical alternative to more sophisticated volumetric segmentation. Additionally, the thresholds used to define response and progression is relatively arbitrary and not optimized based on scientific data showing the best correlation with survival benefit or time to treatment failure.…”
Section: Known Limitations For Current Response Criteriamentioning
confidence: 80%
“…(Note: The efficacy of these thresholds remains to be sufficiently challenged). Also, the use of thresholds based on “percentage change” with respect to baseline tumor size are significantly biased toward small tumors where relatively low absolute changes in tumor size are interpreted as a large percentage change [61]. This is particularly an issue in newly diagnosed GBM studies, where patients with tiny tumors often progress early due to triggering of progression (PD) when “non-measurable disease”, defined as having the two largest perpendicular diameters of a contrast enhancing target lesion less than 10mm, reaches the subtle threshold of “measurable disease”.…”
Section: Known Limitations For Current Response Criteriamentioning
confidence: 99%
“…Biological reasons for why some GBMs grow faster than others are sparsely studied in human patients, which is mainly due to difficulties in acquiring in vivo pretreatment growth estimates [10, 11]. In addition, most research on growth processes have been conducted on in vitro or animal models which fail to accurately imitate the unique micro-milieu of the human GBM [30].…”
Section: Discussionmentioning
confidence: 99%
“…GBMs are characterized by a highly heterogenous histopathology [35], a high secretion of pro-angiogenic factors [6, 7], extensive vascularity [8, 9], and rapid pretreatment growth [10, 11]. The pretreatment growth has been shown to vary considerably among patients [10] and slower growth to be an independent predictor of long term survival in patients with GBM [12].…”
Section: Introductionmentioning
confidence: 99%
“…This is a commonly used glioblastoma tumor volume definition, but it could be seen as a limitation to our study that we lack information about segmentation of tumor in T 2 /FLAIR images. The contrast enhancing compartment, with or without the central necrosis, is currently being used for measuring extent of tumor resection, preoperative tumor growth, and progression of tumors after treatment, as suggested in the RANO criteria [6, 31, 32]. For primary glioblastomas, the most relevant additional tumor compartment to segment would be the edema surrounding the tumor, as seen on T 2 or FLAIR images, which is known to encompass varying degrees of infiltrating tumor cells.…”
Section: Discussionmentioning
confidence: 99%